Bacteria Leaching Process Of The Low-Grade Sulfide Copper Ore - Xie Gang (The Minerals, Metals and Materials Society, 2006)
The leaching experiment used by bacteria on the low grade sulfide copper ore which is difficult to leach was carried out. Some leaching bacteria which have good physiological and leaching activity were isolated and domesticated, and were adapted to leaching ore. The effective domesticated method was put forward. Some technological parameters such as ore acidification, potential controlling, leaching method, ore granularity, leaching acidity, leaching liquid quantity and acid consumption were obtained by column experiment and leaching ore in situ under the ore well. The results show it could leach 30.62% of copper from the low-grade sulfide copper ore within 24 weeks by column leaching method, and the bioleaching rate of copper is 22.83% by leaching in situ under the ore well in 8 months.